Choosing the Best Glasses for Clinical Practice: Evidence- Based Medicine Versus Other Alternative Approaches - Saberi, Masoud (Annals of Anesthesiology and Critical Care, 2016)
Do you belong to the camp of the physicians who wear glasses at work to have a more accurate eyesight? Do you hold the opinion that anyone who does not wear glasses is somewhat categorized as one who does not subscribe to the idea that wearing glasses gives him a sharper view of the world and puts him in a better position to pass judgments? The fact of the matter is that a physician, besides wearing physical eyeglasses, may an advantage of other mechanisms that function as glasses forhimto diagnose the overt andcovertsymptomsfor a variety of diseasesandailments, deeply analyze them, and decide on a prognosis course for each patient accordingly. Students of medicine and their patients habitually carry such metaphorical glasses, and every single one of them gets used to that particular set of lenses over time, resulting in viewing the treatment with their own set of beliefs and biases.